2017
DOI: 10.1021/acs.jpcc.7b08534
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of CeO2 Nanosheets Decorated upon BiOI Microplate: A Surface Oxygen Vacancy Promoted Z-Scheme-Based 2D-2D Nanocomposite Photocatalyst with Enhanced Photocatalytic Activity

Abstract: Construction of a visible light driven Z-schemebased photocatalytic system is a hot topic of research because of the potential to alleviate both energy and environmental issues. In the present study a series of surface vacancy mediated BiOI−CeO 2 nanocomposites were prepared and their crystallographic, morphological, optical, and electrochemical behavior were characterized through XRD, TEM, FESEM, UV−vis DRS, PL, ESI, and Mott−Schottky techniques. From the XPS analysis, it could be said that a high amount of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(78 citation statements)
references
References 66 publications
3
75
0
Order By: Relevance
“…However, the peaks of Bi 4f and I 3d in BiOI nanosheets shifted slightly compared with that of BiOI nanoplates, indicating the formation of the oxygen vacancies . These result was similar to the previous one . Obvious difference in the high resolution XPS of O 1s was observed between BiOI nanoplates and BiOI nanosheets, as shown in Figure 2c.…”
Section: Positron Lifetime Parameters Of Bioi Nanoplates and Bioi Nansupporting
confidence: 84%
See 1 more Smart Citation
“…However, the peaks of Bi 4f and I 3d in BiOI nanosheets shifted slightly compared with that of BiOI nanoplates, indicating the formation of the oxygen vacancies . These result was similar to the previous one . Obvious difference in the high resolution XPS of O 1s was observed between BiOI nanoplates and BiOI nanosheets, as shown in Figure 2c.…”
Section: Positron Lifetime Parameters Of Bioi Nanoplates and Bioi Nansupporting
confidence: 84%
“…The peak at around 529.6 eV is attributed to the Bi‐O bonds in [Bi 2 O 2 ] slabs of BiOI. The other two peaks at around 531.0 and 532.2 eV are assigned to the surface hydroxyl group and oxygen vacancy . Interestingly, the oxygen vacancy peak in BiOI nanosheets is higher than that of BiOI nanoplates.…”
Section: Positron Lifetime Parameters Of Bioi Nanoplates and Bioi Nanmentioning
confidence: 97%
“…14 So, it has enormous potential to be applied for water splitting reaction and environmental pollutant elimination. To date, a number of Z-scheme-based visible light photocatalytic systems have been reported, such as CeO 2 /BiOI, 15 Cu/MoO 3 -g-C 3 N 4 , 16 and LaFeO 3 /g-C 3 N 4 17 possessing much better photocatalytic abilities than single photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above discussed in coupling with g-C 3 N 4 , the bismuth-based 2D layer materials can also be hybrided with other 2D photocatalysts to form 2D/2D heterojunction for the degradation of pollutes. Sultana et al [107] reported a composite of 2D-CeO 2 with 2D BiOI to form a Z-scheme heterojunction for RhB dye decolorization and phenol degradation. In another study, Xu's group [91] designed Au nanoparticles (NPs)-decorated 2D/2D Bi 2 WO 6 -TiO 2 heterostructure (Fig.…”
Section: Removal Of Pollutionsmentioning
confidence: 99%